Reduction ascending aortoplasty: A retrospective analysis of outcomes and risk factors - Szalkiewicz, Philipp; Gökler, Johannes; Dietl, Wolfgang; Ehrlich, Marek; Holzinger, Christoph; Laufer, Günther; Wiedemann, Dominik (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Indication for Reduction Ascending Aortoplasty (RAA) and long-term outcome remain unclear. This study analyzed the outcomes after nonreinforced RAA in two Austrian centers. Methods: Patients with RAA at two Austrian centers between 6/2009 and 6/2017 were retrospectively analyzed. Aortic diameters were measured by computed tomography (CT) pre- and postoperatively. Patients were assigned according to valve morphology and imaging modality. Results: Overall, 253 patients underwent RAA (female: 30.8%; median age 74 [63-79] years) with a mean preoperative ascending diameter of 44.7 (+/- 3.5) mm. RAA-related postoperative adverse events occurred in 1.2% (n=3) over a follow-up of median 3.8 (2.4-5.5) years: One type A aortic dissection, one lethal aortic rupture at the suture line and one suture line bleeding with cardiac tamponade and need of surgical revision. The overall survival rate was 89.7%. Aortic valve morphology itself was no risk factor for mortality (Log-Rank: 0.942). One hundred and forty patients had a tricuspid (TAV: [55.3%]) aortic valve and 113 patients a bicuspid aortic valve (BAV: [44.7%]). Redilatation to a diameter >50 mm according to CT follow-up occurred in 5.7% (n=5 of 87). One patient needed reoperation with RAA and aortic valve replacement due to a prosthesis-patient mismatch after aortic valve replacement and aortic redilatation. Conclusion: Nonreinforced RAA is a safe, feasible and reproduceable procedure with low rates of perioperative complications in selected patients primarily undergoing aortic valve repair with a dilated ascending aorta. Aortic valve morphology has no impact on mortality after RAA.